The Correlation of Diction Mastery and Writing Interest With Students' Writing Ability - Amalisa Amalisa; Tri Riya Anggraini; Eva Nurchurifiani (Master Program in Indonesian Language Education and The Institute for Research and Community Service STKIP PGRI Bandar Lampung, 2022)
The problem was raised in this research is the relationship between mastery of diction and writing interest with the ability to compose narratives. This research was conducted because of the reality on the ground that the ability to compose narratives and mastery of diction, as well as interest in writing, need to be developed. This study aims to describe the relationship between diction mastery and writing interest with the ability to compose narratives for fifth grade students at SDN 4 Tanjung Aman. To achieve the research objectives mentioned above, the authors use the correlational method, meaning that data is collected after all the events in question have taken place. The techniques used in collecting research data are questionnaires, tests, and observations. Research data analysis techniques include requirements analysis test, statistical analysis, and research hypothesis testing techniques. The results of the study show: (1) diction mastery is positively related to the ability to compose narratives as indicated by a correlation coefficient of 0.775 > 0.535 (r table); (2) writing interest is positively related to the ability to compose narratives as indicated by a correlation coefficient of 0.649 > 0.361 ( r table); and (3) mastery of diction and writing interest together have a positive relationship with the ability to compose narrative coefficients of 0.807.